Economics - Truett, Lila J.; Truett, Dale B. (St. Louis : Times Mirror-Mosby College Publishing, 1987)
The book is divided into nine parts: Basic Economic Concepts; The Economics of National Products, Government Spending and Taxation; The economics of money: Banks, Federal Reserve, and National Income; The Economics of Stagflation and Growth; The Economics of Product and Input Markets; The Economics of Government-Business Relationships; The Economics of Internationalism: Trade, Payments, and Growth.
Includes index: p. (1-1 - 1-22)
with 293 illustrations.
Includes bibliographical references.
aia 12/10/2017
Loans
Keywords: Economics